A randomised controlled trial of matrix-assisted laser desorption ionization-time of flight mass spectrometry (MALDITOF-MS) versus conventional microbiological methods for identifying pathogens: Impact on optimal antimicrobial therapy of invasive bacterial and fungal infections in Vietnam - Nadjm, B; Dat, VQ; Campbell, JI; Dung, VTV; Torre, A; Tu, NTC; Van, NTT; Trinh, DT; Lan, NPH; Trung, NV; Hang, NTT; Hoi, LT; et al. (Elsevier, 2019)
OBJECTIVES: We assessed the impact of MALDITOF-MS on the timeliness of optimal antimicrobial therapy through a parallel-arm randomised controlled trial in two hospitals in Vietnam. METHODS: We recruited patients with a pathogen (bacterial or fungal) cultured from a normally sterile sample. Samples were randomly assigned (1:1) to identification by MALDITOF-MS or conventional diagnostics. The primary outcome was the proportion on optimal antimicrobial therapy within 24 hours of positive culture, determined by a blinded independent review committee. Trial registered at ClinicalTrials.gov (NCT02306330). RESULTS: Among 1,005 randomised patients, pathogens were isolated from 628 (326 intervention, 302 control), with 377 excluded as likely contaminants or discharged/died before positive culture. Most isolates were cultured from blood (421/628, 67.0%). The proportion receiving optimal antimicrobial therapy within 24 hours (the primary outcome) or 48 hours of growth was not significantly different between MALDITOF-MS and control arms (135/326, 41.4% vs 120/302, 39.7%; Adjusted Odds ration (AOR) 1.17, p= 0.40 and 151/326, 46.3% vs 141/302, 46.7%; AOR 1.05 p=0.79 respectively). CONCLUSIONS: MALDITOF-MS, in the absence of an antimicrobial stewardship programme, did not improve the proportion on optimal antimicrobial therapy at 24 or 48 hours after first growth in a lower-middle income setting with high rates of antibiotic resistance.